Implementation of healthcare professional credentials in hospitals: A scoping literature review - Tamara, Sena Dwi Tamara; Jiu, Cau Kim; Mardiyani, Ridha; Jais, Suriadi (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Credentialing implementation is a fundamental pillar of clinical governance in hospitals, ensuring that healthcare professionals possess competencies aligned with the clinical privileges granted to them. Despite its critical role in patient safety, the implementation of credentialing processes often encounters various administrative and regulatory challenges. Purpose: To map the existing literature on credentialing implementation processes, regulatory frameworks, barriers, and success factors for healthcare professional credentialing in hospital settings through a scoping review approach. Method: A scoping review design following the PRISMA-ScR guidelines. Article searches were conducted using the Wiley Online Library, PubMed, and ScienceDirect databases, covering publications from 2015 to 2025. After the screening process, 12 articles met the inclusion criteria and were included in the review. Results: A total of 12 articles were analyzed in this review. The findings indicate that the digitalization of credentialing systems and the implementation of Primary Source Verification (PSV) significantly improve the accuracy of competency verification and reduce the risk of malpractice. Regulatory frameworks, such as Medical Staff Bylaws, serve as the primary foundation for accountability in granting clinical privileges. However, barriers including staff resistance to recredentialing, lack of data integration, and limited resources in rural areas remain major challenges. Key success factors were identified as strong hospital leadership commitment and the independence of medical committees in conducting peer review. Conclusion: Effective credentialing implementation requires the integration of transparent policies, robust health information technology infrastructure, and a strong patient safety culture. The findings of this scoping review are expected to serve as a reference for hospital management in optimizing credentialing systems to ensure the quality of healthcare services. Keywords: Credentialing; Clinical Privileges; Clinical Governance; Healthcare Professionals; Hospital.